Humana.mente : journal of philosophical studies - Biblioteca Filosofica (Society) (Biblioteca Filosofica, 2007)
Humana. Mente is a peer-reviewed biannual forum for theoretical and meta-theoretical analysis in philosophy. The journal focuses on the emergent themes at the centre of the philosophical debate. Its principal aim is to foster theoretical dialogue and innovation within the discipline, serving an integrative role for all of those concerned with the evolution of contemporary philosophy.
Keywords: Philosophy : Periodicals; Philosophy; Philosophy